Analysis of Students' Perception in Choosing a Career as an Accountant - Riza Syahputera; Padriyansyah Padriyansyah; Amanda Oktariyani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this study is to identify and analyze the most dominant career choices among students in the accounting field. The research subjects are graduates selected using purposive sampling with the following criteria: graduates from the Accounting Study Program, Faculty of Economics and Business, Tridinanti University in 2022 (having passed their thesis defense), graduates whose contact information could be traced, and graduates who completed the questionnaire in full. The findings reveal that the majority of accounting students at Tridinanti University prefer a career as corporate accountants due to greater job security, alignment with their interests and skills, and a better balance between work and personal life.